Arrest History and Intimate Partner Violence Perpetration in a Sample of Men and Women Arrested for Domestic Violence - Brasfield, Hope (2012)
Abstract: Intimate partner violence (IPV) is a serious and prevalent problem throughout the United States. Currently, individuals arrested for domestic violence are often court mandated to batterer intervention programs (BIPs). However, little is known about the arrest histories of these individuals, especially women. The current study examined the arrest histories of men (n = 303) and women (n = 82) arrested for domestic violence and court-referred to BIPs. Results demonstrated that over 30% of the entire sample had been previously arrested for a non-violent offense, and over 25% of the participants had been previously arrested for a violent offense other than domestic violence. Moreover, men were arrested significantly more frequently for violence-related and non-violent offenses than their female counterparts. In addition, men were more likely than women to have consumed binge-levels of alcohol prior to the offense that led to their most recent arrest and court-referral to a BIP. Lastly, arrest history was positively associated with physical and psychological aggression perpetration against an intimate partner for men only, such that more previous arrests were associated with more frequent aggression. These results provide evidence that many men and women arrested for domestic violence have engaged in a number of diverse criminal acts during their lifetimes, suggesting that BIPs may need to address general criminal behavior